“Alice”: a different environment for learn Object-Oriented Programming - Lucio-Castillo, Mariby (Universidad Autónoma de Tamaulipas, 2011)
This article presents the results generated by an impact study on the education software «Alice» has in teaching object-oriented programming (OOP) in the major of students in computer systems engineering from the Instituto Tecnológico de Ciudad Victoria (ITCV). The purpose of this study was to measure the academic performance of students in courses that use OOP «Alice» in order to assess whether the use of this software tool helps reduce failure rate. The final evaluation results show that in the group of students from ITCV where»Alice» was used as a support tool, the failure rate was 19 % whereas in the group where it was originally used was of 30 %. Following this study, the Facultad de Ingeniería y Ciencias de la Universidad Autónoma de Tamaulipas took the initiative to hold a students work in engineering education in telematics. They used «Alice» to support classroom teaching introductory programming and managed to raise students’ interest in learning to program 90 % to 95 %.